INFLUENCE OF CHROMATOGRAPHY CONDITIONS ON THE RETENTION OF SOME ISOQUINOLINE AND PYRIMIDINONE DERIVATIVES - Ruziev I.Kh; Bebitova K.E; Kilicheva D.M; Kilicheva D.M (Scholar Express Journals, 2023)
In this work, the chromatographic retention of pyrimidinone and isoquinoline derivatives under reversed-phase HPLC conditions was studied. Retention and separation factors were determined for various eluent compositions (CH3CN and H2O). The dependence of retention on the concentration of the organic modifier in the mobile phase was studied. In addition, studiedretention of the studied components depending on the nature of the substituents and their mutual arrangement.
Keywords: Is quinolines; pyrimidinones; RP HPLC